A latent variable investigation of the Phonological Awareness Literacy Screening-Kindergarten assessment: Construct identification and multigroup comparisons between Spanish-speaking English-language learners (ELLs) and non-ELL students. (April 2014) - Huang, Francis L.; Konold, Timothy R.
Psychometric properties of the Phonological Awareness Literacy Screening for Kindergarten (PALS-K) instrument were investigated in a sample of 2844 first-time public school kindergarteners. PALS-K is a widely used English literacy screening assessment. Exploratory factor analysis revealed a theoretically defensible measurement structure that was found to replicate in a randomly selected hold-out sample when examined through the lens of confirmatory factor analytic methods. Multigroup latent variable comparisons between Spanish-speaking English-language learners (ELLs) and non-ELL students largely demonstrated the PALS-K to yield configural and metric invariance with respect to associations between subtests and latent dimensions. In combination, these results support the educational utility of the PALS-K as a tool for assessing important reading constructs and informing early interventions across groups of Spanish-speaking ELL and non-ELL students.